Canada/CARICOM Scholarship Program : interim training and financial report (The Group MontrealCA, 1992)
Covers the period April 1, 1992 to September 30, 1992. Provides information on training activities, financial information on planned and actual expenditures for the period and forecasts expenditures to the end of fiscal year 1992-93.
DC